Analisis Tingkat Kerawanan Banjir Menggunakan Metode Weighted Overlay Berbasis Sistem Informasi Geografis (SIG) di Kecamatan Ulu Ogan Kabupaten Ogan Komering Ulu - Adisty Merisya Putri; Harnani; Dwi Vina Febrim (Mataram University, 2026)
Flooding in the Ulu Ogan Subdistrict, Ogan Komering Ulu Regency, is generally triggered by high rainfall that causes the rivers in Ulu Ogan to overflow. This study aims to analyze the level of flood vulnerability in Ulu Ogan Subdistrict, Ogan Komering Ulu Regency, by utilizing a Geographic Information System (GIS) based on overlay and scoring methods. The overlay method is used to combine various relevant spatial data layers, such as slope gradient, land use, soil type, rainfall, and distance to rivers. Each parameter is assigned a weight and score based on its level of contribution to flood potential, and then integrated to produce a flood vulnerability zoning map. The research area in Ulu Ogan Subdistrict, Ogan Komering Ulu Regency, is dominated by a high level of flood vulnerability. The high vulnerability zone covers approximately 16,987.59 ha (70.19%), the moderate vulnerability zone covers 6,691.86 ha (27.65%), and the low vulnerability zone covers 522.9 ha (2.16%).